Associations Between Online Purchasing and Store Purchasing for Four Types of Products in Nanjing, China. Issue 1 (2016) - Zhen, Feng; Cao, Xinyu (Jason); Mokhtarian, Patricia L.; Xi, Guangliang
As e-shopping proliferates, transportation planners examine the extent to which it will replace shopping trips. Although previous studies have explored relationships between online purchasing and store purchasing, few have examined the relationships for different types of products in China. A joint ordered probit model was applied to investigate the relationships among 963 respondents in Nanjing, China. Online purchasing had positive associations with store purchasing for all four types of products (clothing, books, daily goods, and electronics), even after shopping attitudes and demographics were controlled for. The magnitude of the complementarity effect differs by product type, with less frequently purchased products showing a larger effect. The impact of online purchasing on road systems is limited in China because transit and walking are dominant modes for shopping trips. However, the impact is expected to grow.